Role of Persistent Diarrhea Control in Declining Infant and Childhood Mortality in Indonesia - Rusdi Ismail (Indonesian Pediatric Society Publishing House, 2018)
In diarrheal diseases control program (CDD), the mechanism of diarrheal diseases (DD) death can be classified into: dehydration, dysentery, complication, and persistent diarrhea. The aim of the presentation is to predict the share of these components and to highlight the role of persistent diarrhea. Demographic figures were inferred from the Census and the 1985 Inter-Censal Survey data. Rates on DD were inferred from the National Household Health Surveys and relevant reports. The mechanisms of death were inferred from the pattern of DO death in Palembang General Hospital. By fair prediction, in infants, 1.5 lives will be saved per 1000 live births through COD Program, 88% is the share of persistent diarrhea control, and 20% of better management of DD complicated with other diseases. In 1-4 years of age, the figures are 68% and 38%, respectively. The share of promoting rehydration and dysentery management will be minimal in declining infant mortality rate (MR) and childhood death rate (CDR) between 1992 and 2000. The share of COD in declining IMR and CDR must depend on a better management of persistent and complicated DD.